Fish Biodiversity and Substrate Composition on Coral Reef Ecosystem at Penimbangan, Buleleng Regency, Bali - Sapto Andriyono; Diah Ayu Safitri; Akhmad Taufiq Mukti; Mike van Keulen (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The Penimbangan is one of the potential locations for underwater tourism in the Regency Buleleng, by unique dive spot. Planning and sustainable coastal development are essential for the continuity ecosystem, sea, and economy. Fish and coral studies in Penimbangan, District Buleleng, occurred from December 2022 to February 2023. Location observation shared four sites of data retrieval. The determination sites study uses purposive sampling based on the spread of coral naturally. Data was collected by Underwater Photo Transect (UPT) for coral and Underwater Visual Census (UVC) for fish. Transect area coral 50m long with quadratic transect (58cmx44cm), and classified categories using CPCe software. Transect area fish of 350 m2 (length 70 m, limit right and left 2.5 m), identified fish to level species. The most studied habitat associations in coral reefs are coral (HC) and fish in coral assemblages. Percentage composition substrate basis in Penimbangan, namely dead coral with algae (106.74), coral (90.27), and sand (70). Lifeform coral is found in as many as ten types; the most are CM (39.00), CE (23.20), and ACS (10.07). A total of 17 families with 70 reef fish species were recorded in this study. The family with the most species is Pomacentridae (25), followed by Chaetodontidae (9) and Labridae (8). The composition of fish will vary according to the type of habitat. Different coral habitats covered by benthic influence the abundance of certain trophic levels of reef fish in an area of water.